Evaluation of a Diagnostic Therapeutic Educational Pathway for Asthma Management in Children and Adolescents - Guarnaccia, Sebastiano; Quecchia, Cristina; Festa, Andrea; Magoni, Michele; Zanardini, Elena; Brivio, Valentina; Scarcella, Carmelo; Gretter, Valeria; Gasparotti, Cinzia; Frassine, Malica; Ferrari, Martina; Limina, Rosa Maria; et al. (Frontiers in Pediatrics, 2020)
BACKGROUND: Limited evidence exists for the effectiveness of educational programs that improve pediatric asthma control in real world settings. We aimed to assess the impact of a diagnostic, therapeutic and educational pathway (DTEP) for asthma management in children and adolescents attending an asthma referral center. METHODS: This is a retrospective population-based cohort study, including two groups of patients with asthma, aged 6-17 years and residing in the Local Health Authority (LHA) of Brescia, Italy: a) the children who followed a DTEP (intervention group) and b) all the children residing in the LHA who did not follow DTEP (control group). The incidence rates (IRs) of hospitalization, emergency room visit, use of outpatient services and drug prescription for dyspnea, wheezing, or respiratory symptoms were computed for time before and after attending DTEP in the intervention group, and for “early” and “late” time since asthma diagnosis in the control group. RESULTS: 9191 patients were included in the study, 804 of which followed DTEP. In the before-DTEP/early time, the interventions and control groups showed similar IRs for all the outcomes apart from emergency room visits (IRs of 138.6 and 60.3 per 1000 person-years, respectively). The IRs decreased from before to after DTEP and from early to late time in both groups. The IR decrease for emergency room visits was significantly higher in the intervention than control group (-51.3% and -28.2%, respectively, IRR=0.61; p=0.001). CONCLUSION: The DTEP can increase patients’ capability in managing asthma and preventing the exacerbations of their diseases.